Systematic review on mobile applications in adherence to the treatment of patients with heart failure (Research, Society and Development, 2020)
The study aimed to evaluate the effectiveness of using mobile applications in adhesion to the treatment of patients with chronic heart failure. This is a systematic review of the literature, in which the search was conducted in April 2020, in the databases PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Scopus, Virtual Health Library and Web of Science. The following descriptors were used: heart failure, mobile applications and patient compliance, requiring adaptations to meet the specificities of the bases. 74 studies were identified and after applying the selection criteria, six publications reached the level of quality for inclusion and synthesis. The reviewed articles demonstrate a significant change in medication adherence, based on personalized telemonitoring, especially with elderly participants. With this study, the use of mobile applications in the management of the health of patients with heart failure is recommended to improve adherence and self-care.